El proceso inflacionario en el Ecuador: un análisis de sus determinantes con modelos Arima y Vectores autorregresivos - Erráez , Juan Pablo (2020)
The present paper tries to explain the determinants of the inflation from the beginning of the implementation of the official dollarization until December 2004. This investigation was design for the desire of deepening the econometrics methodologies that allow to give an appropriate treatment of macroeconomic time series in order to define economic policies based on technical approaches that facilitate the economic development of the Ecuador in the XXI century.